Ultimate Strength Analysis of Laminated Composite Sandwich Plates. (June 2018) - Anish,; Kumar, Ajay
Abstract: The ultimate strength analysis of laminated composite sandwich plates is presented via ultimate failure load prediction along with modes of failure for laminated composite sandwich plates using mathematical model based on improved higher order shear deformation theory (IHSDT). The proposed IHSDT mathematical model satisfies the inter-laminar shear stress continuity at each layer interface and also ensures zero transverse shear stress conditions at the plate top and bottom. The piecewise parabolic shear stress variation across the thickness of each layer is considered. No shear correction factors are required. The suitable C0 FE formulation of IHSDT model is developed by authors.